PERAN STAKEHOLDER DALAM MENDUKUNG IMPLEMENTASI KEBIJAKAN KAMPUNG KELUARGA BERENCANA: STUDI DESA JAMBEWANGI KECAMATAN SEMPU KABUPATEN BANYUWANGI - Eko Setyo Widodo; Kris Nugroho (Jurnal Politik indonesia (Indonesian Journal of Politics), 2021)
The family planning village in Jambewangi village of Banyuwangi regency has been awarded the title of provice and national pilot KB Village in the year of 2019. Motivated by the commitment and active role of various components of stakeholders to foster and accompany the society in the process of implementation of the KB village policy. All stakeholders involved can provide coaching and facilitation to improve the utilization of all potential of the welfare and acceleration of the development of Jambewangi village. Each stakeholder involved has different influences and interests. It is also influenced by power or authority over the policy itself. This study was qualitative with a descriptive approach. Data were collected using observation and deep interviews. After examining the validity, data were analyzed by presenting the data that is simultaneously analyzed and interpreted according to the analysis theory of stakeholder role to be concluded. This study explains the analysis of the role of stakeholders involved in the implementation of family planning village in Jambewangi village of Banyuwangi regency, which are grouped based on interests and power on policies in accordance with Bryson's stakeholder analysis theory. From the results of this study, it was concluded that the grouping of stakeholders in this study had the aim to find out the parties involved in the implementation of the policy including its roles, interests, and impacts arising from the implementation of the policy program.